Heat Transfer Analysis of Modified Solar Collector Plate with Mini-Channel (Journal of University of Babylon for Engineering Sciences, 2018)
In this paper, experimental and numerical analyses have been executed to investigate the thermal performance of modified design of mini-channel plate solar collector. For the application of mini-channel heat exchangers, it is necessary to have perfect design tools for predicting the pressure drop and heat transfer. A numerical model combining solar radiation with convective heat transfer to the absorber plate based on mini-channel has been developed. Reynolds number ranged from 70 to 300 at the fluid flow rate ranged from 4.6 L/h to 18.35 L/h is used for experimental investigation at fluid inlet temperature (20°C); the working fluid is propylene glycol. The mini channel solar collector performance is evaluated in terms of heat transfer coefficient, Nusselt number, friction factor, and pumping power. The result revealed that when there is an increase in the mass flow rate of flowing fluid, the convective heat transfer coefficient is increased, while the friction factor is decreased.